Tabrīz, Iran. Die Südbastion auf dem Gelände des Rabʿ-i Rashīdī: Untersuchungen zur Baugeschichte. Die Arbeiten des Jahres 2017 - Fuchs, Christian (e-Forschungsberichte des DAI, 2017)
The recently agreed Iranian-German joint program „Rabʿ-e Rashīdī“ in Tabrīz started with first systematic prospections, analyses and sondages around the fortress, focusing in particular the massive “South Tower” that was presumably erected in the 16th century by Shāh Abbās. Indeed, the area is carrying the name of Rashīd al-Dīn who founded here in the early 14th century a huge endowment inclusive mosque, university and other religious and academic institutions by order of the ruling Ilkhanid Ġāzān Khan. The agreement comprises support in the restauration of the visible still massive buildings and in establishment of touristic infrastructures since the city of Tabriz is elected as the Iranian capital of Tourism and Cultural Heritage in 2018, and is kindly supported by the president of the DAI, F. Fless. First investigations that focus the South Tower in the center of the area indicate a much more complex building history and possible secondary utilization of the bastion and its surrounding annexes. It appears most likely that we can find preceding phases of the whole complex earlier than the 16th century but also subsequent annexes and building phases that are not directly linked with the character of a fortification.